Macartney at Kashgar : New Light on British, Chinese and Russian Activities in Sinkiang, 1890-1918. - Nightingale, Pamela (Taylor and Francis, 2013)
First published in 1973. This book describes the career of Sir George Macartney, who spent twenty-eight years at the turn of the nineteenth century as British representative in Sinkiang, China's most westerly province. Macartney was in a unique position to observe political and diplomatic manoeuvres by the key players trying to establish a sphere of influence in China's strategically vital hinterland before and during the Chinese revolution.